Atividade da quitotriosidase em pacientes com paracoccidioidomicose crônica - Gustavo Gomes Martins (2013)
Introduction: The paracoccidioidomycosis (PCM) is a systemic infectious disease caused by Paracoccidioides brasiliensis and one of the most important systemic mycosis endemic in Latin America. The criteria for cure of paracoccidioidomycosis are not well defined. The enzyme chitotriosidase (QT) is naturally produced in human macrophages and belongs to the class of chitinases. The increase in activity is related to activation of macrophages in diseases of inflammatory nature. The P. brasiliensis has chitin as a component of its cell wall, being susceptible associate elevation of QT with the activity of PCM. Objective: The aim of this study is to correlate the increased activity of QT with chronic active PCM, and evaluate its utility as a biomarker of this mycosis. Methods: We selected two groups of patients:1. chronic untreated PCM group: 14 patients, 2. Control group: 14 healthy people who voluntarily donated blood for the study. The QT was measured in fluorescence assay. Results: The QT activity was considerably higher in the first compared to the second group (P <0.001). The medians (in nmol / ml / h) for the PCM group and control were respectively 174 (± SD 122) and 44 (SD ± 29). Discussion: The QT activity is elevated in systemic fungal infections, parasitic and bacterial diseases in lysosomal storage and inflammatory processes. Their role in the human immune system seems to be related to innate immunity and its regulation appears complex, involving Th1 and Th2 lymphocytes and cytokines. The variation of serum QT may be a way of inferring the activity of various inflammatory processes, including fungi, which can help as a biomarker of PCM. Conclusion: The QT can be in simple method to reveal the presence of inflammatory response associated with fungal infection. Further tests are necessary to relate clinical-laboratory increased activity of QT as a biochemical marker in PCM.